PENERAPAN FULL COSTING UNTUK EFISIENSI BIAYA DAN DAYA SAING UMKM - Tuti Setiatin; Niken Safitri; Ebah Suaebah (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy. However, many MSMEs, including Tiktak Kencur Nenk Tasya, still face challenges in financial management and the implementation of proper accounting practices, particularly in recording production costs. Previously, the cost recording at this MSME only covered daily raw material expenses, neglecting overhead costs and indirect labor, which resulted in inaccuracies in calculating the Cost of Goods Manufactured (COGM). This inaccuracy can affect pricing decisions, profit margins, and competitiveness. This research aims to design an effective cost recording system and determine the optimal COGM for Tiktak Kencur Nenk Tasya MSME. The full costing method is applied, as it is recognized for providing more accurate accounting by clearly classifying production costs. This study adopts a descriptive quantitative approach with a case study method, collecting data through observation, interviews, and documentation. The results of the COGM calculation using the full costing method for January 2025 show a total finished goods production cost of IDR 160,080,000 for 12,000 kg of products, resulting in a unit cost of approximately IDR 13,340.7. The estimated cost of work-in-process at the end of the period is IDR 6,489,000, bringing the total production cost for that month to IDR 166,569,000. Accurate implementation of COGM is expected to assist MSMEs in planning, financial management, improving competitiveness, and operational efficiency.